2020
DOI: 10.1108/ijchm-04-2020-0349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating hotel websites through the use of fuzzy AHP and fuzzy TOPSIS

Abstract: Purpose The purpose of this study is to develop a useful, effective and comprehensive approach to facilitate the evaluation of hotel websites. Design/methodology/approach The paper examines the literature evaluating e-commerce sites, particularly that is focused on hotel, tourism and travel. Moreover, 5 criteria and 19 sub-criteria are identified, and a two-step method is proposed for the assessment of hotel websites whereby the global weights of the proposed criteria are determined by the fuzzy analytic hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 49 publications
1
22
1
1
Order By: Relevance
“…Ramyar, Hamzah and Halim (2020) used the VlseKriterijumska Optimizacija I Kompromisno Resenje under fuzzy environment (FVIKOR) technique to assess the website quality of four hotels in Iran. Baki (2020) attempted to create a system for assessing hotel websites using the fuzzy analytic hierarchy process (FAHP) and the fuzzy technique for order preference by similarity to ideal scenario (FTOPSIS). Samanlioglu, Burnaz, Dis, Tabas and Adıguzel (2020) used a combination of the Fuzzy bestworst method (FBWM) and FTOPSIS to evaluate and rate the websites of Paloma hotels in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramyar, Hamzah and Halim (2020) used the VlseKriterijumska Optimizacija I Kompromisno Resenje under fuzzy environment (FVIKOR) technique to assess the website quality of four hotels in Iran. Baki (2020) attempted to create a system for assessing hotel websites using the fuzzy analytic hierarchy process (FAHP) and the fuzzy technique for order preference by similarity to ideal scenario (FTOPSIS). Samanlioglu, Burnaz, Dis, Tabas and Adıguzel (2020) used a combination of the Fuzzy bestworst method (FBWM) and FTOPSIS to evaluate and rate the websites of Paloma hotels in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The top 10 hotels that obtained five stars in 2021, according to the customer reviews on the website http://www.boutiquesmallhotels.com/ are included in the evaluation. In addition, 16 criteria are selected based on past website evaluation research in the literature (Ip, Law, & Lee, 2012;Akincilar & Dagdeviren, 2014;Ostavara & Shahraki, 2019;Roy, Sharma, Kar, Zavadskas & Saparauskas, 2019;Baki, 2020;Ramyar et al,2020;Mahdi & Esztergár-Kiss, 2021). Table 1 shows the criteria determined.…”
Section: Applicationmentioning
confidence: 99%
“…They support the idea that before making the decision to adopt an innovation, potential adopters first look for a benefit from it and the greater the perceived benefit of an innovation is, the faster its adoption rate is likely to be. Baki (2020) carried out a study on the evaluation of hotel websites. His study showed that special discounts are among the most important criteria to convert a visitor into an effective customer.…”
Section: Proposed Conceptual Frameworkmentioning
confidence: 99%
“…Therefore, different dimensions and attributes may be considered whilst measuring the performance of a website. Similarly, when tourism or hotel websites have been evaluated, the measurements used in different studies are divergent [4,12].…”
Section: Website Evaluationmentioning
confidence: 99%